Dynamic uncertainty and global warming risk - Francesco Bosello; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 1999)
When economic agents decide their optimal environmental behavior, they have to take into account non continuos evolutionary trends and irreversible changes characterising environmental phenomena. Given the still non perfect biophysical and economic knowledge, decisions have to be taken in an uncertain framework. The paper analyses in the specific how agents' optimal choices are affected by the presence of a future possible, but uncertain catastrophic occurrence provoked by a climate collapse due to global warming.
Keywords: C5; D8; D9; O2; Q2; 330; Climate change; irreversibility; endogenous-exogenous uncertainty; Prinzipal-Agent-Theorie; Risiko; Klimawandel; Theorie